Developing Students’ Speaking Skill Through Storytelling Technique - Marhamah M.S (International Journal of Educational Research Excellence, 2025)
This research aims to (1) develop students’ speaking skills through storytelling and (2) determine whether storytelling can develop students’ speaking skills through storytelling. (3) To explain the process of developing speaking skills through storytelling. The population of the research was students of STITBA (Babussalam Tarbiyah High School) Southeast Aceh. The sample consisted of 33 students in the second semester. The samples were collected using purposive sampling. The research was a Research and Experimental Development (R&D), which was conducted by conducting two tests: pre-test and post-test. A Pre-test was given before implementing story “Malin Kundang” while post-test was given after implementing story “ Putri Betung”. Both qualitative and quantitative methods were used in this study. Data were analyzed using t-tests. After the data had been collected using the test, it was found that the pre-test average was 50,43 while the post-test was 78,14. There was a 15% improvement in the pre-test value. Thus, the authors concluded that there were improvements in the speaking skills of students through the storytelling technique. This can also be proved by comparing the result t observation (2,077) with t table (2,030) for alpha = 5%. This means that the hypothesis was supported.